An exploratory study on the election perception of Generation Z in Türkiye - Yaman, Haluk; Orhan, Ertuğrul Buğra (IGI Global, 2025)
In an environment where technological developments are very intense, it is impossible for Generation Z not to be affected by technology. Political socialization, which is one of the socialization stages, is also affected by the relations between peers along with technological developments. In line with the social constructivist perspective, this paper aims to measure the influence of X5 (Twitter) on Generation Z's perceptions of choice. Uses and gratifications theory guided the formulation of semi- structured interview questions. As a result of the interviews, Generation Z's experiences on the positive and negative consequences of their use of Twitter on their electoral perceptions were shown. It was observed that members of Generation Z did not position themselves outside politics and emphasized that their political behavior should be carried to a participatory level for their expectations to be realized. © 2025, IGI Global Scientific Publishing. All rights reserved.
Keywords: Exploratory studies; Political behaviors; Semi structured interviews; Technological development; Uses and gratifications theories; Social networking (online)